Perubahan Paradigma Guru dalam Pengelolaan Kinerja di Platform Merdeka Mengajar - Helmawati, Helmawati; Dermawan, Hendra; Nurwulan, Tyara Ratna; Susanti, Asti; Abhirama, Trian Fhakar (Universitas Indraprasta PGRI Jakarta, 2025)
This study aims to examine the paradigm shift of teachers in performance management through the Merdeka Mengajar Platform. In line with the advancement of technology and evolving educational policies, especially in the era of digital transformation, Merdeka Mengajar Platform has become a key platform for teachers to enhance the quality of learning. This research employs a qualitative approach with case studies from several schools that have implemented the platform. The data were collected through in-depth interviews, observations, and document analysis related to the implementation of Merdeka Mengajar Platform in classrooms. The findings indicate that the use of this platform encourages teachers to adapt to technology-based learning approaches, focusing on autonomy, innovation, and the enhancement of professional skills. Teachers have started managing their performance more efficiently, developing more creative teaching methods, and becoming more responsive to students' needs. This paradigm shift also impacts time management and learning evaluation, making them more flexible and data-driven. Thus, the study concludes that Merdeka Mengajar Platform not only facilitates teachers in managing their performance but also significantly contributes to improving the quality of education in Indonesia.